Ultrasensitive NOx optoelectronic sensor - Wojtas, Jacek; Bielecki, Zbigniew; Stacewicz, Tadeusz; Czyżewski, Adam; Mikołajczyk, Janusz; Nowakowski, Mirosław; Rutecka, Beata (Photonics Letters of Poland, 2009)
The paper presents opportunities of application of Cavity Enhanced Absorption Spectroscopy (CEAS) technique in nitrogen oxides (NOx) detection. The CEAS technique is a modification of Cavity Ring Down Spectroscopy (CRDS) technique. It is based on off-axis arrangement of an optical cavity. In this system, an absorbing gas concentration is determined due to decay time measurement of a light pulse trapped in a optical cavity. Measurements are not sensitive to laser power fluctuation and photodetector sensitivity fluctuation. Setup includes the resonance optical cavity, build with spherical mirrors of high reflectance. As light sources pulsed lasers are used. NOx detection is carried out in the visible and infrared range. The signal is registered with specially developed low noise photoreceiver. The features of a designed sensor show that it is possible to build an optoelectronic trace gases sensor, which sensitivity could be comparable with chemical sensors. Such system has several advantages; relatively low price, small size and weight, and possibility of detection of other gases and explosive materials.